Global burden of chronic kidney disease and its attributable risk factors (1990-2021): an analysis based on the global burden of disease study - Li, Min-Jia; Liu, Hong-Yong; Zhang, Yun-Qiang; Li, Sheng-Rong; Zhang, Jian-Hong; Li, Rong (Frontiers in Endocrinology, 2025)
BackgroundChronic kidney disease is a global health challenge, especially in resource-limited regions. Understanding its burden and key risk factors is crucial for effective interventions.MethodsData from the Global Burden of Disease Study (1990–2021) covering 204 countries were analyzed to assess trends in prevalence, mortality, and disability-adjusted life years for chronic kidney disease, alongside geographic, age, sex, and risk factor patterns.FindingsIn 2021, an estimated 674 million individuals were affected globally. Although the global age-standardized prevalence rate declined slightly by 0.8% since 1990, substantial disparities persisted. High-income North America’s prevalence remained stable yet showed high mortality (20.6 per 100,000) and increased DALYs (508.8 per 100,000). In contrast, East Asia’s prevalence fell by 11.7%, accompanied by notable reductions in mortality (11.1 per 100,000) and DALYs (322.4 per 100,000). Regions with low socio-demographic indices, including parts of sub-Saharan Africa and South Asia, bore the greatest burdens, with persistently high prevalence (exceeding 9000 per 100,000) and rising DALYs. Some countries, such as Guatemala, experienced rapid prevalence increases, while others, like Italy, achieved substantial reductions. Similarly, mortality trends varied: Ukraine saw steep increases, while Poland showed marked improvements. DALY burdens also diverged, with El Salvador experiencing large increases, and Kuwait recording significant declines. Prevalence peaked at ages 65–69 in males and 70–74 in females, with female rates surpassing male rates from the early thirties onward. High fasting plasma glucose contributed 36% of DALYs globally, heavily affecting the Caribbean and high-income North America. High systolic blood pressure and high body mass index were particularly influential in Central Europe and high-income North America, respectively. Low fruit intake strongly affected the Middle East and East Asia.InterpretationThese findings underscore persistent global inequalities in CKD outcomes, necessitating region-specific strategies and strengthened healthcare capacity to mitigate the burden.